Exploring the relationship between teacher work engagement and organizational citizenship behavior in early childhood education - Yixuan Zhao; Connie Shin (International Journal of Evaluation and Research in Education (IJERE), 2026)
The role of teacher work engagement (TWE) is very important in creating positive organizational citizenship behavior (OCB) within the early childhood education (ECE) context. This study hypothesizes the use of TWE structural equation modeling (SEM) with advanced logistic regression (ALR) (TWE-SEM-ALR) model and predict the occurrence of OCB among teachers. When 250 early childhood educators in both public and privates collected a teacher-based questionnaire data, it was observed that the information was gathered in questionnaires. Evaluation was done through experimental means, where an 80:20 train-test splitting was used. The model with the suggested accuracy of 92.4 and precision of 0.91, recall as 0.93, F1-score as 0.92, and area under the curve (AUC) of 0.95 was better than models based on logistic regression, support vectors machines, and SEM-only models. The error analysis and the ablation studies also served to validate the role of every model component, as it was shown that the combination of SEM and ALR greatly minimizes the error in predictions and enhances classification stability. The findings of the effectiveness of the proposed framework in explaining complex engagements-behavior relationships and it has rich implications to educational administrators who wish to improve teacher performance and organizational performance.